Parf: Adaptive Parameter Refining for Abstract Interpretation - Wang, Zhongyi; Yang, Linyu; Chen, Mingshuai; Bu, Yixuan; Li, Zhiyang; Wang, Qiuye; Qin, Shengchao; Yi, Xiao; Yin, Jianwei (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2024)
Abstract interpretation is a key formal method for the static analysis of programs. The core challenge in applying abstract interpretation lies in the configuration of abstraction and analysis strategies encoded by a large number of external parameters of static analysis tools. To attain low false-positive rates (i.e., accuracy) while preserving analysis efficiency, tuning the parameters heavily relies on expert knowledge and is thus difficult to automate. In this paper, we present a fully automated framework called Parf to adaptively tune the external parameters of abstract interpretation-based static analyzers. Parf models various types of parameters as random variables subject to probability distributions over latticed parameter spaces. It incrementally refines the probability distributions based on accumulated intermediate results generated by repeatedly sampling and analyzing, thereby ultimately yielding a set of highly accurate parameter settings within a given time budget. We have implemented Parf on top of Frama-C/Eva - an off-the-shelf opensource static analyzer for C programs - and compared it against the expert refinement strategy and Frama-C/Eva's official configurations over the Frama-C OSCS benchmark. Experimental results indicate that Parf achieves the lowest number of false positives on 34/37 (91.9%) program repositories with exclusively best results on 12/37 (32.4%) cases. In particular, Parf exhibits promising performance for analyzing complex, large-scale real-world programs.CCS CONCEPTS* Software and its engineering → Automated static analysis.